(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
According to the author the purpose of the study is totest empirically the conceptualization of consumer brand evaluation:brandimage, brand attitude and perceived quality of a soft drink which isconsidered as a non-durable product. Ten attributes have been taken intoconsideration for the study. The findings support brand evaluation for the sameproduct using different factors. Results of the study might be useful to academicians, manufacturers, andother applied researchers.